Accelerating Practical Digital Development in the Solomon Islands - World Bank (World Bank, Washington, DC, 2021)
This report first describes the value to be derived from an increasingly digital economy in the Solomon Islands and examples of how other countries are doing the same. The tourism, agriculture, and fisheries sectors are examined in detail. It then presents an assessment of the digital government program elements and the extent to which they contribute to delivering effective and efficient, digitally enhanced government operations and services. Finally, and most importantly, it presents an assessment of the status and issues of the foundational enablers of a digital economy. The outcomes of the assessment indicated that while continued attention and action are required on digital government program elements, the SIG needs to focus mainly on strengthening the enabling environment for both digital government and the digital economy. Recent developments suggest good progress, (i.e. the National ICT Policy, the submarine cables, cybersecurity committee and planning), but several of the enablers require investment, effort, and action. The results of this assessment, and the breadth of the resulting recommendations, are further evidence of the degree of effort needed to accelerate the establishment of a digital economy and a digital government in the Solomon Islands, beyond simply the provision of faster, cheaper internet access. However, this assessment also exposes an already-substantial level of sophistication, continuing progress on key areas of focus, and a strong political will to invest additional resources and effort. The Prime Minister signaled his strong support in the Solomon Islands Digital Economy Workshop held in early November 2019. The arrival of the submarine cable, together with the recommended actions from the workshop and those provided herein, will no doubt accelerate the realization of the vision of ‘A peaceful, united and progressive Solomon Islands communicating and informed by technologies open to all’. The global COVID-19 pandemic has further underscored the importance of accelerating digital development, particularly in the Pacific Islands region. Since March 2020 this region has been particularly isolated by travel restrictions, and severe disruptions across all economic sectors. The issues described in this report remain highly relevant, particularly regarding the urgency of improving digital infrastructure (connectivity), enabling digital payments, boosting digital skills, and enacting legislation to protect digital transactions and safeguard privacy.